Analisis Pembuatan Alat Pembersih Filter Udara pada Truk Hino dengan Metode Rasional di PT. XYZ - Indiyono, Lalak; Cahyono, Manggi Dwi; Arnol, M Yusuf; Oja, Karrolus Borromeus Wake Wara Leta (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This research focuses on the analysis of the design and manufacture of an air filter cleaning tool for Hino trucks using compressed air as the cleaning medium. Generally, the air filter cleaning process is carried out by spraying air from the outside to the inside, so that some dust remains in the deepest layer of the filter. In this research, a tool was developed that allows the air spray direction to be reversed, namely from the inside of the filter to the outside, so that dirt particles can be removed more effectively. Test results conducted at PT. XYZ showed that cleaning time can be shortened from three minutes to one minute, with more optimal cleaning results. This tool is manually operated and all components are made from very strong local materials. This innovation is expected to be widely implemented in commercial vehicle workshops in Indonesia to improve efficiency, work safety, and the effectiveness of air filter maintenance.